PENGARUH MODERNISASI SISTEM ADMINISTRASI DAN TRANSPARANSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK BADAN (Studi Kasus pada Kantor Pelayanan Pajak Pratama Semarang Timur) - Zahra Dinul Khaq; Imam Setijawan (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study aims to determine empirically : 1 ) the influence of modernization of the tax administration system on tax compliance body , 2 ) the effect of tax transparency on tax compliance entities listed in STO East Semarang. Sources of data in the research is a primary data obtained from the questionnaires of WP Agency shaped CV and PT are listed in STO East Semarang . The method used is quantitative method with a survey approach . The sampling technique in this study using a convenience sampling technique . The analytical method used is multiple regression analysis . Partial hypothesis testing using t test and simultaneously by using F test with a significance level ( α ) of 0.05 . The results showed that the modernization of the tax administration system significantly influence taxpayer compliance. And transparency of taxation significant effect on taxpayer compliance. Keywords : Administration of taxation, taxpayers Compliance , Modernization, Transparency , taxpayer .